2018
DOI: 10.1016/j.jairtraman.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for preferred seat selection on UK domestic flights

Abstract: This study employs a stated preference method to elicit and explore customer willingness to pay for airline ancillary products, specifically seat selection fees. Bivariate correlations are used to investigate linkages between passenger attributes and opinions with stated values for seat selection under a range of scenarios on UK domestic services.The sensitivity of consumers to ticket fares, for both business and non-business travel, is found to be negatively correlated with the stated willingness to pay for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Profit from payable seat selection occupies a great proportion of ancillary profit. Rouncivell et al [3] utilized UK domestic flights to study the willingness to pay for airline seat selection. They found that ticket fare was an important factor for both business and non-business travel and that passengers who chose the service in the past were more likely to choose it again.…”
Section: Seat Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Profit from payable seat selection occupies a great proportion of ancillary profit. Rouncivell et al [3] utilized UK domestic flights to study the willingness to pay for airline seat selection. They found that ticket fare was an important factor for both business and non-business travel and that passengers who chose the service in the past were more likely to choose it again.…”
Section: Seat Selectionmentioning
confidence: 99%
“…With the development of airline business, ancillary services [1][2][3][4][5][6][7] that satisfy passengers' personal requirement are becoming increasingly important for airlines. Ancillary revenue has already played a vital role in airline profit and greatly increases the amount of extra financial revenue for airlines.…”
Section: Introductionmentioning
confidence: 99%
“…As such, literature has shown that dynamically priced ancillary fees could increase airline revenue. For example, airlines could increase seat reservation fee revenues by dynamically pricing seats, such as increasing seat prices as a flight departure date approaches or varying prices based on a seat’s location on the plane (Mumbower et al 2015 ; Rouncivell et al 2018 ; Shao et al 2020 ). Also, Shaban et al ( 2019 ) propose a model of dynamically priced extra-baggage services that accounts for utilization-level of the cargo belly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional customer purchase behavior findings include that customer choice of premium seats with extra legroom are impacted by load factor, as customers are more likely to purchase premium seats when the free window and aisle seats are all full (Mumbower et al 2015 ). Customers value window seats, aisle seats, and seats in the front of the plane the most and will pay to avoid sitting in a middle seat (Mumbower et al 2015 ; Rouncivell et al 2018 ; Shao et al 2020 ). Customers also value extra legroom more on long-haul routes than on shorter routes (Mumbower et al 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By the 2080s, the number of infrastructure assets exposed to flooding more frequently than 1:75 years on average is expected to increase by 30% (under a 2°C climate change projection) and by 200% under a 4°C projection, and the length of railway lines exposed to flooding is expected to increase by 53 and 160% (under 2°C and 4°C climate change projections, respectively, for flooding more frequent than 1:75 years on average) [20]. Another example is flying; overall UK aviation activity grew by 17.8% between 2006 and 2016 [54]. There are several recent examples of how flooding has impacted aviation infrastructure and passengers, including Christmas Eve 2013 and the heavy rainfall that led to flooding and the outage of the three airportoperated electrical substations at Gatwick Airport, leading to flight cancellations that impacted more than 13 000 passengers [55].…”
Section: (I) Fluvial Systems and Processes: Environmental Regulationmentioning
confidence: 99%